ІМІТАЦІЙНЕ МОДЕЛЮВАННЯ ФУНКЦІОНУВАННЯ БАЛАНСУЮЧОГО РИНКУ ЕЛЕКТРОЕНЕРГІЇ З УРАХУВАННЯМ СИСТЕМНИХ ОБМЕЖЕНЬ НА ПАРАМЕТРИ РЕЖИМУ ОЕС УКРАЇНИ - Блінов, І.В.; Парус, Є.В.; Іванов, Г.А. (Інститут електродинаміки НАН України, Київ, 2017)
The description of the basic principles of constructing of the means of imitation modeling of the balancing electricity market functions in Ukraine is described. The assumptions, which are base of the imitation model of the balancing market are identified. The main functions of the imitation model of the balancing market and the mathematical apparatus used for the realization of these functions are outlined. An example of the modeling results of balancing market functions, taking into account the network constraints of the IPS of Ukraine is presented. References 6, figures 4.